A nota amarela, seguida de "Sobre a escrita - um ensaio à moda de Montaigne" - Czekster, Gustavo Melo (2020)
The present thesis is composed of two distinct and interacting moments. The first part, the fictional creation, consists of a novel, A nota amarela [The yellow note], which presents a story told from the point of view of Jacqueline du Pré (1945-1987), a cellist who, during a performance of Elgar’s Cello Concerto, questions aspects of her individual quest to try to bring the perfect music that inhabits her imagination into the world. Amongst such thoughts, the narrator recalls a myth dating back to Imperial China regarding the existence of a yellow note, the note of Creation. Therefore, believing that such a sound is hidden within all human beings, she decides to look for it within herself, which ends up leading her to a number of personal problems and discoveries. The second part of the thesis, represented by the academic essay written based on Michel de Montaigne’s essays, presents some technical aspects regarding the construction of the novel A nota amarela, such as the origin of the work of art, the genesis of the creative impulse, the advantages and the difficulties in dealing with real characters, and also the perception of narrative time as part of the structure of the work and the notion of event as a central point of fiction. Furthermore, the essay discusses some of the problems that the author encountered while carrying out the literary work and how they were tackled throughout the plot.